A pressure ulcer and fall rate quality composite index for acute care units: A measure development study. (November 2016) - Boyle, Diane K.; Jayawardhana, Ananda; Burman, Mary E.; Dunton, Nancy E.; Staggs, Vincent S.; Bergquist-Beringer, Sandra; Gajewski, Byron J.
Abstract: Background: Composite indices are single measures that combine the strengths of two or more individual measures and provide broader, easy-to-use measures for evaluation of provider performance and comparisons across units and hospitals to support quality improvement. Objective: The study objective was to develop a unit-level inpatient composite nursing care quality performance index—the Pressure Ulcer and Fall Rate Quality Composite Index. Design: Two-phase measure development study. Settings: 5144 patient care units in 857 United States hospitals participating in the National Database of Nursing Quality Indictors ® during the year 2013. Methods: The Pressure Ulcer and Fall Rate Quality Composite Index was developed in two phases. In Phase 1 the formula was generated using a utility function and generalized penalty analysis. Experts with experience in healthcare quality measurement provided the point of indicator equivalence. In Phase 2 initial validity evidence was gathered based on hypothesized relationships between the Pressure Ulcer and Fall Rate Quality Composite Index and other variables using two-level (unit, hospital) hierarchical linear mixed modeling. Results: The Pressure Ulcer and Fall Rate Quality Composite Index   =   100  −  PUR  −  FR, where PUR is pressure ulcer rate and FR is total fall rate. Higher scores indicate better quality. Bland-Altman plots demonstrated agreement between pairs of experts and provided evidence for inter-rater reliability of the formula. The validation process demonstrated that higher registered nurse skill mix, higher percent of registered nurses with a baccalaureate in nursing or higher degree, higher percent of registered nurses with national specialty certification, and lower percent of hours supplied by agency staff were significantly associated with higher Pressure Ulcer and Fall Rate Quality Composite Index scores. Higher percentages of unit patients at risk for a hospital-acquired pressure ulcer and higher unit rates of physical restraint use were not associated with higher Pressure Ulcer and Fall Rate Quality Composite Index scores. Conclusions: The Pressure Ulcer and Fall Rate Quality Composite Index is a step toward providing a more holistic perspective of unit level nursing quality than individual measures and may help nurses nursing administrators obtain a broader view of which patient care units are the higher and lower performers. Further study is needed to examine the usability of the Pressure Ulcer and Fall Rate Quality Composite Index.